The 21 most powerful minutes in a leader's day revitalize your spirit and empower your leadership - Maxwell, John C. (Thomas Nelson, 2007)
In the spirit of his best-selling The 21 Irrefutable Laws of Leadership and The 21 Indispensable Qualities of a Leader, John Maxwell offers thoughts on proven leadership qualities and crucial issues that affect leadership success. These basic principles of success can be applied to business and private life, helping anyone reach their full potential. Twenty-one powerful statements help leaders maximize their assets and overcome their weaknesses, encouraging them to lead with their hearts as well as their minds. Daily readings include sections which help readers integrate and apply each day's material.